2018
DOI: 10.1111/cuag.12220
|View full text |Cite
|
Sign up to set email alerts
|

An Extension Specialist's Reflections from the Field: Discovering Ag of the Middle in the Shift from Direct Sale to Wholesale Vegetable Production

Abstract: Although consumer demand for local and organic food continues to grow, some direct market outlets have tightened.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…This finding is supported by the results of earlier research, which show that more farmers are producing organically certified food due to the growing local demand for it (Thompson and Gaskin, 2018). Farmers have been prompted to accept organic certification to market their tea due to the strong demand for organic tea among the Chinese population as a sign of their status (James et al , 2019).…”
Section: Resultssupporting
confidence: 76%
“…This finding is supported by the results of earlier research, which show that more farmers are producing organically certified food due to the growing local demand for it (Thompson and Gaskin, 2018). Farmers have been prompted to accept organic certification to market their tea due to the strong demand for organic tea among the Chinese population as a sign of their status (James et al , 2019).…”
Section: Resultssupporting
confidence: 76%
“…This is smaller than mid-scale production for fruits and vegetables in California of 8–101 ha (20–250 acres) for which production is year-round (Minor and Bond, 2017; Esquivel et al, 2021). Mid-scale fruit and vegetable production in our study area would be closer to the range of 4–20 ha (10–49 acres) used to characterize mid-scale production in the state of Georgia (Thompson and Gaskin, 2018). Urban expansion could likely necessitate buffering from roads and other surrounding infrastructure by 2050, an important consideration for future projections.…”
Section: Methodsmentioning
confidence: 99%
“…Mid-scale production of table foods could support environmentally beneficial practices as well as economic benefits for producers (Thompson and Gaskin, 2018). Environmentally, mid-scale agricultural producers in the USA more readily include ecological diversification and adopt conservation practices that could enhance ecosystem services which support increased social benefits (Esquivel et al, 2021).…”
Section: Spatial Visualization Of Peri-urban Food Systemsmentioning
confidence: 99%
“…Jablonski et al (2022) reported similar findings, noting that direct marketing is quite labor-intensive. In a proof-of-concept project intended to evaluate the economic feasibility of shifting from a diversified direct-market cropping system to one tailored for wholesale accounts (fewer crops and more mechanization), Thompson and Gaskin (2018) demonstrated that small growers could feasibly produce for a wholesale market on small acreage and without sacrificing environmental production values. On a more qualitative level, Silva et al (2015) found that farmers selling in intermediated markets are more satis-fied with their profitability than those selling into direct-market channels.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%